Model Pembelajaran Problem Based Learning Mampu Meningkatkan Kemampuan Analisis Siswa - Jumini Jumini (Journal of Informatics and Vocational Education, 2022)
The objective of research conducted at Karanganyar Vocational High School using the Problem-Based Learning (PBL) learning model is to 1) enhance students' analytic abilities and 2) increase student participation in creating side presentation materials with Canva. The design employed is quasi-experimental approach with a Pre-test and Post-test using two cycles with the planning, implementation, observation, and reflection stages. The subjects of this study were thirty-five students in tenth grade. Using instruments in the form of observation sheets and pre- and post-tests containing analysis and observation questions to assess the implementation of teaching and learning activities based on the PBL model. According to the findings of this study, the process of teaching and learning activities using the PBL model increased by 19.3% from cycle 1 to cycle 2, from 64.7% to 82.35%. Therefore, PBL was able to enhance students' analytical abilities.